Short Communication : Validation of rapid DNA extraction protocol and their effectiveness in marker assisted selection in crop plants - Singh, Vivek K.; Singh, Vikas K.; Ellur, Ranjith K.; Krishnan, S. Gopala; Singh, Ashok k. (The Indian Journal of Genetics and Plant Breeding, 2016)
In the present study, a simple and ultra quick protocol for extraction of genomic DNA was successfully validated in four different crops namely rice, wheat, lentil and Indian mustard.The method is simple and involves only two steps, it does not involve use of liquid nitrogen and other expensive and toxic reagents, and is highly suited for analyzing large number of samples within a short span of time.This makes it very attractive for use in MAS even in smaller labs where no sophisticated facilities are available.